Fergana Valley Vine Studies of Parasitic Nematodes - A. G. Abdurakhmanova; N. S. Ergasheva (American Journal of Biology and Natural Sciences, 2024)
This article presents information about the survey of the parasitofauna of the vineyards of Forgona voxa. Soil samples were taken from the depths of 0-20, 20-40, 40-60 cm of the soil around the roots. Generally accepted phytohelminthological methods were used to isolate nematodes from soil. The root of the plant was examined with binoculars. The work of analysis before the species was carried out with the preparation of permanent, temporary preparations. Parasitofauna of the examined vineyards consisted of 3 genera and 7 species. Virus-carrying ectoparasitic nematodes were detected from around the roots of the infected vine.